Permitting Pornography. A Critical Review of the History of Pornography Censorship in Iceland in a European Perspective - Ásta Guðrún Helgadóttir 1990- (2014)
Part of this research will be published in the summer 2014 in "Porn Studies", a journal published by Routledge. This dissertation will discuss Iceland's approach toward pornography censorship in a European perspective. The Icelandic laws banning pornography production and distribution date back to an article from 1869 and no substantial revisions have been made since then, only further additions to the article. The laws have generally been considered to be deadletter laws, but have received a new life in the 21st century as the main antagonist in the quest for Internet censorship. Iceland became synonymous with prestigious reform of laws relating to freedom of expression following a banking crisis in 2008 and consequently became reputable as a data and media haven. This dissertation examines the origins of the anti-pornography laws in Iceland, how they have been applied, and why they have remained stagnant compared to the development of laws on pornography in other European states. This dissertation puts forth that the anti-pornography feminist discourse on the laws was adopted by the more conservative judicial system and that it, at the same time, suited traditional attitudes of a portion of the general public. The censorship of pornography has not only been a contested issue from a moral point of view, but also contested are the technical possibilities of censorship on the Internet. The issue is many layered and it has to be examined from several perspectives: in context of legal history, social development, feminist theories, and what censorship actually means in the era of the Internet.